Improvement of the encoding information method for pharmaceutical products QR-codes during sorting on a robotic conveyor line - Nevliudov, I. Sh.; Klymenko, O. M.; Yevsieiev, V. V.; Maksymova, S. S. (Національний технічний університет "Харківський політехнічний інститут", 2025)
The article presents an improved encoding information method for QR-codes, designed to increase the efficiency of robotic conveyor lines for sorting pharmaceutical products. The proposed solution is based on the use of the redundancy operator and random permutation algorithms, which allows reducing the number of errors during reading, increasing the resistance of QR codes to mechanical damage and reducing processing time. The conducted studies demonstrate an increase in sorting accuracy by 35% and a decrease in the frequency of failures by 25%, which provides significant optimization of production processes and improved reliability of automated systems. У статті представлено вдосконалений метод кодування інформації у QR-кодах, розроблений для підвищення ефективності роботи роботизованими конвеєрними лініями сортування фармацевтичної продукції. Запропоноване рішення базується на використанні оператора надмірності та алгоритмів рандомної перестановки, що дозволяє зменшити кількість помилок під час зчитування, підвищити стійкість QR-кодів до механічних пошкоджень і скоротити час обробки. Проведені дослідження демонструють підвищення точності сортування на 35% та зниження частоти збоїв на 25%, що забезпечує значну оптимізацію виробничих процесів і покращення надійності автоматизованих систем.
Удосконалення методу кодування інформації у QR-кодах фармацевтичної продукції при сортуванні на роботизованій конвеєрній лінії
Keywords: QR-code; robotic conveyor line; pharmaceutical products; information encoding; redundancy operator; resistance to damage; automation; sorting; QR-код; роботизована конвеєрна лінія; фармацевтична продукція; кодування інформації; оператор надмірності; стійкість до пошкоджень; автоматизація; сортування